Pendampingan Pelatihan Jurnalistik untuk Meningkatkan Wawasan Literasi Siswa SMA Negeri 1 Pabedilan Kabupaten Cirebon - Nuary, Muhammad Guruh (Edujavare Publishing, 2023)
Increasing literacy among high school students is becoming increasingly important in today's information age, especially in mastering critical and accurate journalistic skills. However, many students still lack practical training in this field. This study aims to improve the literacy insight of students at SMA Negeri 1 Pabedilan, Cirebon Regency through structured journalism training assistance. This training program includes news writing, interviews, and article editing, and emphasizes journalistic ethics and information responsibility. The method used is Community-Based Research (CBR), which involves students, teachers, and schools in designing and implementing training in July - August 2023. Students are directly involved in the journalistic process, from data collection to news publishing, with guidance and feedback from experts. Evaluation is carried out through observation and assessment of student work results, as well as interviews to assess changes in their understanding and journalistic skills. The results of the training showed a significant increase in students' news writing, interviewing, and editing skills. In addition, their understanding of journalistic ethics and ability to analyze news also increased. This program succeeded in motivating students to be more involved in journalistic activities outside the classroom. In conclusion, this practice-based journalism training is effective in improving high school students' journalism literacy and can be used as a model for similar training programs in the future.